Managing customer retention in the UK online banking sector. (15th January 2007) - Liu, Liu; Louvieris, Panos
The aim of the research is to investigate the factors that affect customers' continued usage of UK online banking services. From the Technology Acceptance Model (TAM), perceived usefulness and perceived ease of use have been shown to be important factors in determining the acceptance of various internet technologies. However, this model does not fully explain the customers repeat usage behaviour towards internet banking services. This study augments the original TAM by adding two variables, trust and commitment, as well as adapting the model to cover customer retention for online banking. Based on a survey of 196 UK student users, the results strongly support an adapted TAM for online banking in predicting customers' continued usage. Moreover, sustainable repeat usage is a form of habitual behaviour which requires minimal cognitive effort to drive the action tendency towards continued usage; hence, a conative oriented form of TAM is employed.